The Role Of Multicultural Education In Language Attitudes And Politeness - Eli, Nur Eliza; Riskha Arfiyanti (Universitas Swadaya Gunung Jati, 2025)
Indonesia is a country that is rich in cultural, religious, ethnic andlanguage diversity. With this diversity, there is a demand forunderstanding and appreciation for these differences. One way iswith multicultural education. This study aims to find out how muchthe role of multicultural education in shaping attitudes andpoliteness in language. This research method uses a descriptivequalitative approach with a literature study method taken from thejournals in the Google Scholar database. The results showed thatmulticultural education became a crucial approach in instillingattitudes and politeness in language as a form of respect for thediversity of culture, religion, ethnicity, and race in Indonesia.Multicultural education is integrated in the curriculum in order toform awareness of the importance of politeness in language in thecontext of diversity